Case Report: Pediatric age onset CNTN1 antibody-associated neuropathy with nephropathy and literature review - Bayraktar Eltutan, Ceyda; Rinaldi, Simon; Vural, Atay; Aksu, Bagdagul; Maras Genc, Hülya; Pembegul Yildiz, Edibe (Frontiers in Immunology, 2025)
We present a 12-year-old boy with acute onset sensorimotor neuropathy and membranous glomerulonephritis associated with contactin-1 antibodies. This prompted us to explore the clinical characteristics of this condition and assess whether its presentation differs between pediatric and adult patients. A comprehensive search was conducted across multiple online databases, including PubMed and EMBASE, using MeSH terms such as “chronic inflammatory demyelinating polyradiculopathy”, “acute inflammatory demyelinating polyradiculopathy “, “CIDP”, “Guillain Barre syndrome”, “proteinuria”, “nephrotic syndrome”, “nephropathy”, “renal disease”, “glomerulonephritis”, “membranous nephropathy”, “autoimmune nodopathies”, and “membranous glomerulonephritis”. We reviewed publications up to October 2024 and identified 39 patients with anti-contactin associated CIDP (chronic inflammatory demyelinating polyradiculopathy) with membranous glomerulonephritis (MGN), including our case. This rare coexistence typically occurs at advanced ages, with only two pediatric cases. Clinical features were similar regardless of age at onset. We compared the onset, symptoms, progression, renal histopathology, and treatment responses between pediatric and adult patients.